High-performance continuous casting tundish dry material forming method
By drying and vibrating the raw materials of the slag raw materials and adjusting the vibration and baking parameters according to the particle size distribution, the problems of low forming strength and efficiency of the slag raw materials in the prior art are solved, and higher strength and longer service life are achieved.
Patent Information
- Application Number
- CN202510386951.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-03-31
AI Technical Summary
During the molding process of existing bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb-type bulb
By drying the candidate raw materials after crushing and grinding, the dried particle size distribution is obtained, and the vibration parameters and baking control parameters are determined according to the particle size distribution, including vibration time, vibration frequency, heating rate, baking temperature and baking time, to ensure that the density of the candidate raw materials meets the preset standards.
It improves the strength and molding efficiency of the slag material, extends its service life, and ensures uniformity and tightness after molding.
Smart Images

Figure CN119910741A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of continuous casting tundish metallurgy, and in particular to a high-performance continuous casting tundish dry material forming method. Background Art
[0002] The tundish is an intermediate storage device for molten steel to be diverted from the ladle to the crystallizer during the steelmaking and continuous casting process. It is crucial to ensure clean steelmaking and multi-furnace continuous casting. As an important refractory material for the tundish working lining in the steel continuous casting industry, the tundish dry material has an important influence on the preparation of high-performance and quality steel. The service life of the tundish dry material is relatively long, generally up to more than 20 hours, and up to 60-70 hours. Therefore, the application of dry materials has become more and more extensive in recent years. During the use of the tundish, it will be continuously eroded by molten steel and impacted by slag, which will affect the service life of the tundish dry material, thereby affecting the continuous casting industry. Since the dry material does not contain water and has sufficient strength after low-temperature baking, it can be used for cold ladle casting. In addition, it has the advantages of not polluting the molten steel, long service life, simple maintenance, and easy ladle cleaning.
[0003] For continuous casting production, improving the operating rate of the continuous casting machine means increasing production and increasing benefits. High-efficiency continuous casting technology is centered on high casting speed and based on high-quality, defect-free billet production. However, in the actual production process, there are many factors that limit the efficient production of continuous casting. The existing refractory materials of the tundish are of poor quality, which seriously pollutes the quality of molten steel and also reduces the quality of the billet. The life of the tundish also seriously restricts the number of continuous casting furnaces, which not only reduces the molten steel recovery rate, but also reduces the number of continuous casting furnaces of the continuous casting machine. The tundish dry material adopts the construction process of vibration molding and baking solidification. If the strength after baking is low, it will cause local collapse of the dry material and the generation of large cracks, which makes the tundish dry material have poor slag resistance and short service life. How to improve the strength and corrosion resistance of the tundish dry material is a technical problem that urgently needs to be solved in the current industry.
[0004] Chinese patent publication number CN115417661B discloses a tundish dry material, a tundish working lining and a preparation method thereof, wherein refractory aggregate and lightweight filler are first mixed, inorganic fiber, fine powder additive and inorganic binder are added and mixed for a second time, then a surface modifier is added and mixed for a third time, and finally a dust suppressant is added and mixed for a fourth time, and the tundish dry material is obtained by placing the tundish dry material in a sealed container for vacuum storage; the tundish dry material is poured between the permanent layer and the fetal membrane of the tundish, vibrated and compacted, and then heated and baked, and the fetal membrane is pulled out after the fetal membrane is cooled to obtain the tundish working lining.
[0005] It can be seen that the above invention has the following problems: the vibration parameters and baking parameters in the intermediate bag dry material forming process are fixed empirical values, but the parameters of the intermediate bag dry material after each mixing may be inconsistent, it is difficult to ensure the strength of the intermediate bag dry material, and the forming efficiency is relatively low. Summary of the invention
[0006] To this end, the present invention provides a high-performance continuous casting tundish dry material forming method to overcome the problems in the prior art that it is difficult to ensure the strength of the tundish dry material and the forming efficiency is relatively low.
[0007] To achieve the above object, the present invention provides a high-performance continuous casting tundish dry material forming method, comprising: Step S1, crushing and grinding the raw materials, and stirring and mixing them according to the formula ratio to obtain candidate raw materials; Step S2, drying the candidate raw material and obtaining the particle size distribution of the candidate raw material after drying; Step S3, determining vibration parameters during the vibration process according to the particle size distribution, and performing vibration treatment on the dried candidate raw material based on the vibration parameters; the vibration parameters include vibration time and vibration frequency; Step S4, obtaining the volume density and apparent porosity of the candidate raw material after vibration, and determining whether the density of the candidate raw material after vibration meets a preset standard according to the volume density and apparent porosity; Step S5, if the density of the candidate raw material after vibration meets the preset standard, determining the baking control parameters of the baking process based on the bulk density and the apparent porosity; the baking control parameters include heating rate, baking temperature and baking time; Step S6, baking the candidate raw material based on the determined baking control parameters, and cooling the candidate raw material after baking to obtain a formed tundish dry material.
[0008] Further, in step S3, determining the vibration parameters during the vibration process includes: Step S31, determining a particle size characteristic value according to the particle size distribution; Step S32, comparing the particle size characteristic value with a preset particle size value, and determining the vibration parameters during the vibration process based on the comparison result.
[0009] Furthermore, in the step S32, determining the vibration parameters during the vibration process further includes: If the particle size characteristic value is greater than the preset particle size value, increasing the preset vibration parameter to obtain each vibration parameter in the vibration process; If the particle size characteristic value is less than or equal to the preset particle size value, the preset vibration parameter is reduced to obtain each vibration parameter in the vibration process; wherein the preset vibration parameter is the vibration parameter in the vibration process corresponding to the preset particle size value.
[0010] Furthermore, in the step S32, the increase / decrease amplitude of the preset vibration parameter is determined according to the difference between the particle size characteristic value and the preset particle size value.
[0011] Further, in step S4, if the volume density is greater than the preset volume density, and the apparent porosity is less than the preset apparent porosity, the density of the candidate raw material after vibration meets the preset standard; otherwise, the density of the candidate raw material after vibration does not meet the preset standard.
[0012] Furthermore, after step S4, the method further includes: Step S41, if the density of the candidate raw material after vibration does not meet the preset standard, repeat step S3 to perform vibration treatment.
[0013] Further, in the step S5, determining baking control parameters of the baking process based on the bulk density and the apparent porosity includes: The volume density and the apparent porosity are input into a target neural network model to obtain baking control parameters output by the target neural network model.
[0014] Further, in the step S5, determining baking control parameters of the baking process based on the bulk density and the apparent porosity includes: Step S51, determining a parameter adjustment ratio based on the volume density and the apparent porosity; Step S52, determining the baking control parameters of the baking process based on the parameter adjustment ratio and the preset baking control parameters.
[0015] Furthermore, in step S6, it includes: The demoulding strength of the candidate raw material after baking is detected, and whether the baking is completed is determined based on the demoulding strength.
[0016] Further, in the step S6, a cooling rate of the cooling process is determined based on the baking control parameter.
[0017] Compared with the prior art, the beneficial effect of the present invention is that the present invention can remove moisture and avoid expansion and rupture of the intermediate bag dry material by drying the candidate raw materials after crushing, grinding and mixing, thereby improving the strength and molding efficiency of the intermediate bag dry material after molding. By determining the vibration parameters through the particle size distribution after drying, not only can the particles in the dry material be rearranged to form a dense and uniform whole, thereby improving the strength of the intermediate bag dry material, but also the vibration and molding efficiency can be improved. By judging whether the density of the candidate raw materials after vibration meets the preset standards, the uniformity and tightness of the intermediate bag dry material can be further ensured. The baking control parameters of the baking process are determined by the volume density and apparent porosity after vibration, and the baking process can be flexibly controlled according to the various parameters after vibration, thereby improving the strength and molding efficiency of the intermediate bag dry material, and can extend the service life of the intermediate bag dry material.
[0018] Furthermore, the present invention determines a particle size characteristic value according to the particle size distribution of the candidate raw material after drying, and determines a vibration parameter in the vibration process according to a comparison result between the particle size characteristic value and a preset particle size characteristic value, which can not only improve vibration accuracy and vibration flexibility, but also improve molding efficiency.
[0019] Furthermore, the present invention determines whether the density of the candidate raw material meets the preset standard based on the relationship between the bulk density and the preset bulk density, as well as the relationship between the apparent porosity and the preset apparent porosity, which can improve the accuracy of the determination, thereby improving the subsequent molding quality and molding efficiency.
[0020] Furthermore, the present invention repeats step S3 to perform vibration treatment by determining that the density of the candidate raw material after vibration does not meet the preset standard, which can improve the density of the dry material in the tundish to improve its strength, thereby extending the service life of the dry material in the tundish.
[0021] Furthermore, the present invention determines whether baking is complete based on the demoulding strength of the candidate raw material after baking, which can improve the strength and molding efficiency of the tundish dry material.
[0022] Furthermore, the present invention determines the cooling rate of the cooling process based on the baking control parameters, which can avoid cracks caused by too fast temperature changes and reduce thermal expansion and contraction caused by temperature changes, thereby improving the strength of the dry material in the tundish and extending its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of a high-performance continuous casting tundish dry material forming method according to an embodiment of the present invention; Figure 2 A schematic diagram of the steps in determining the vibration process according to an embodiment of the present invention; Figure 3A logic judgment diagram for determining the vibration process in an embodiment of the present invention; Figure 4 A schematic diagram of the steps of determining baking control parameters of a baking process according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0026] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.
[0027] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0028] See also Figure 1 As shown, it is a flow chart of a high-performance continuous casting tundish dry material forming method according to an embodiment of the present invention; the present invention provides a high-performance continuous casting tundish dry material forming method, comprising: Step S1, crushing and grinding the raw materials, and stirring and mixing them according to the formula ratio to obtain candidate raw materials; It is understandable that those skilled in the art know that any equipment and method in the prior art that can crush, grind and stir the raw materials of the tundish dry material falls within the protection scope of the present invention and will not be described in detail here.
[0029] During implementation, the actual implementers can set the formula ratio according to the actual situation, for example: 20 to 35 parts of waste magnesium old bricks, 20 to 35 parts of calcined forsterite; 50 to 70 parts of sintered magnesia particles, and 5 to 10 parts of metal iron powder.
[0030] Step S2, drying the candidate raw material and obtaining the particle size distribution of the candidate raw material after drying; It is understandable that by drying the candidate raw materials, moisture can be quickly removed, and during the drying process, some components in the candidate raw materials will gradually solidify, and after drying, a loose and uniform candidate raw material will be obtained, thereby improving the bonding strength of the candidate raw materials and improving the molding efficiency.
[0031] In practice, the actual implementers can determine the drying parameters according to the actual situation or based on the grinding degree / components and contents in the candidate raw materials. Preferably, the drying time is 1 h to 2 h, and the drying temperature is 800° C. to 1000° C.
[0032] It should be noted that those skilled in the art know that any method in the prior art that can determine the particle size distribution of the candidate raw material after drying falls within the protection scope of the present invention and will not be described in detail herein.
[0033] Step S3, determining vibration parameters during the vibration process according to the particle size distribution, and performing vibration treatment on the dried candidate raw material based on the vibration parameters; the vibration parameters include vibration time and vibration frequency; See also Figure 2 and Figure 3 As shown, Figure 2 A schematic diagram of the steps in determining the vibration process according to an embodiment of the present invention; Figure 3 The logic judgment diagram for determining the vibration process in the embodiment of the present invention; specifically, in the step S3, determining the vibration parameters in the vibration process includes: Step S31, determining a particle size characteristic value according to the particle size distribution; Step S32, comparing the particle size characteristic value with a preset particle size value, and determining the vibration parameters during the vibration process based on the comparison result.
[0034] In implementation, the particle size characteristic value is the particle size value corresponding to the cumulative distribution (the percentage of particles smaller than a certain particle size) in the candidate raw material after drying being greater than the first preset threshold. Preferably, the value range of the first preset threshold is set to 80% to 90%.
[0035] Specifically, in step S32, determining the vibration parameters during the vibration process also includes: If the particle size characteristic value is greater than the preset particle size value, increasing the preset vibration parameter to obtain each vibration parameter in the vibration process; If the particle size characteristic value is less than or equal to the preset particle size value, the preset vibration parameter is reduced to obtain each vibration parameter in the vibration process; wherein the preset vibration parameter is the vibration parameter in the vibration process corresponding to the preset particle size value.
[0036] Specifically, in step S32, the increase / decrease amplitude of the preset vibration parameter is determined according to the difference between the particle size characteristic value and the preset particle size value, wherein the difference between the particle size characteristic value and the preset particle size value is positively correlated with the increase / decrease amplitude of the preset vibration parameter.
[0037] It can be understood that the actual implementers can set the preset particle size value according to the actual situation or based on the particle size distribution of the dried candidate raw materials corresponding to the intermediate bag dry materials that have passed the qualification test in the historical data. Preferably, the preset particle size value can be set to 4 / 5 to 9 / 10 of the average of the maximum particle sizes of the dried candidate raw materials that have passed the qualification test in the historical data; the actual implementers can set the preset vibration parameters according to the actual situation or based on the average of the vibration parameters of the preset particle size values corresponding to the intermediate bag dry materials that have passed the qualification test in the historical data during the vibration process. Preferably, the value range of the preset vibration time is set to 5min to 10min, and the value range of the preset vibration frequency is set to 50Hz to 80Hz.
[0038] In implementation, the adjustment ratio can be determined based on the ratio of the difference between the particle size characteristic value and the preset particle size value to the preset particle size value, and the increase / decrease amplitude of the preset vibration parameter can be determined based on the product of the adjustment ratio and each preset vibration parameter.
[0039] In a specific embodiment, the first preset threshold is 80%, the preset particle size value is 0.7 mm, the preset vibration time is set to 7 min, the preset vibration frequency is set to 63 Hz, and the particle size distribution of the candidate raw material after drying is 70% for a particle size below 0.5 mm and 85% for a particle size below 0.8 mm. The particle size characteristic value is 0.8 mm, and the particle size characteristic value (0.8 mm) is greater than the preset particle size value (0.7 mm). The preset vibration parameters are increased to obtain the vibration parameters in the vibration process. The adjustment ratio is (0.8-0.7) / 0.7=1 / 7. The increase in vibration time is (1 / 7)×7=1 min, and the increase in vibration frequency is 63×7=9 Hz, that is, the adjusted vibration time is 7+1=8 min, and the adjusted vibration frequency is 63+9=72 Hz.
[0040] It should be noted that those skilled in the art are aware that any device and method in the prior art that can vibrate the dried candidate raw material falls within the protection scope of the present invention and will not be described in detail herein.
[0041] The present invention determines a particle size characteristic value according to the particle size distribution of the candidate raw material after drying, and determines a vibration parameter in the vibration process according to a comparison result between the particle size characteristic value and a preset particle size characteristic value, which can not only improve vibration accuracy and vibration flexibility, but also improve molding efficiency.
[0042] Step S4, obtaining the volume density and apparent porosity of the candidate raw material after vibration, and determining whether the density of the candidate raw material after vibration meets a preset standard according to the volume density and apparent porosity; Specifically, in step S4, if the volume density is greater than the preset volume density, and the apparent porosity is less than the preset apparent porosity, the density of the candidate raw material after vibration meets the preset standard; otherwise, the density of the candidate raw material after vibration does not meet the preset standard.
[0043] It should be noted that the bulk density refers to the ratio of the mass of the candidate raw material after vibration to its total volume, and the apparent porosity is the ratio of the volume of all open pores in the candidate raw material after vibration to its total volume. Those skilled in the art know that any method and device in the prior art that can measure the bulk density and apparent porosity of the candidate raw material after vibration falls within the protection scope of the present invention and will not be described in detail herein.
[0044] It is understandable that the actual implementer can set the preset volume density and preset apparent porosity according to the actual situation or based on the average of the volume density and apparent porosity of the candidate raw materials after vibration corresponding to the intermediate bag dry materials that have passed the qualification test in the historical data. Preferably, the value range of the preset volume density is set to 1.8 g / cm 3 ~2.5g / cm 3 , the preset apparent porosity range is set to 40% to 50%.
[0045] The present invention determines whether the density of the candidate raw material meets the preset standard based on the relationship between the bulk density and the preset bulk density and the relationship between the apparent porosity and the preset apparent porosity, which can improve the accuracy of the determination and thus improve the subsequent molding quality and molding efficiency.
[0046] Specifically, in step S4, it also includes: Step S41, if the density of the candidate raw material after vibration does not meet the preset standard, repeat step S3 to perform vibration treatment.
[0047] In implementation, if the volume density is less than or equal to the preset volume density, or the apparent porosity is greater than or equal to the preset apparent porosity, the density of the candidate raw material after vibration does not meet the preset standard, and the candidate raw material is vibrated again according to step S3 until the density of the candidate raw material after vibration meets the preset standard.
[0048] The present invention repeats step S3 to perform vibration treatment by determining that the density of the candidate raw material after vibration does not meet the preset standard, which can improve the density of the dry material in the tundish to improve its strength, thereby extending the service life of the dry material in the tundish.
[0049] Step S5, if the density of the candidate raw material after vibration meets the preset standard, determining the baking control parameters of the baking process based on the bulk density and the apparent porosity; the baking control parameters include heating rate, baking temperature and baking time; Specifically, in a specific embodiment, in the step S5, determining the baking control parameters of the baking process based on the volume density and the apparent porosity includes: The volume density and the apparent porosity are input into a target neural network model to obtain baking control parameters output by the target neural network model.
[0050] In implementation, training samples are generated according to the volume density and apparent porosity corresponding to each tundish dry material that has passed the qualification test in the historical data, sample labels corresponding to each training sample are generated according to the corresponding baking control parameters, and the initial neural network model is trained according to each training sample and the corresponding sample label to obtain the target neural network model. It should be noted that those skilled in the art know that any neural network model in the prior art that can obtain baking control parameters through training falls within the protection scope of the present invention and will not be described in detail here.
[0051] See also Figure 4 , which is a schematic diagram of the steps of determining the baking control parameters of the baking process in an embodiment of the present invention; specifically, in another specific embodiment, in the step S5, the baking control parameters of the baking process are determined based on the volume density and the apparent porosity, including: Step S51, determining a parameter adjustment ratio based on the volume density and the apparent porosity; Step S52, determining the baking control parameters of the baking process based on the parameter adjustment ratio and the preset baking control parameters.
[0052] In implementation, a first comparison value is determined according to the ratio of the volume density to a preset volume density, a second comparison value is determined according to the ratio of the apparent porosity to a preset apparent porosity, and a parameter adjustment ratio is determined according to the product of the first comparison value and the second comparison value.
[0053] It can be understood that the actual implementers can set the preset baking control parameters according to the actual situation or based on the average values of the baking control parameters corresponding to the intermediate package dry materials that have passed the qualification inspection in the historical data. Preferably, the value range of the preset heating rate is set to 800℃ / h~1000℃ / h, the value range of the preset baking temperature is set to 1000℃~1300℃, and the value range of the preset baking time is set to 2h~4h.
[0054] The baking control parameters of the baking process are determined according to the product of the parameter adjustment ratio and the preset baking parameters. For example, the preset heating rate is 900°C / h, the preset baking temperature is 1200°C, the preset baking time is 3h, the ratio of the bulk density to the preset bulk density is 1.2, and the ratio of the apparent porosity to the preset apparent porosity is 0.8. The parameter adjustment ratio is 1.2×0.8=0.96, and the heating rate of the baking process is 0.96×900=864°C / h, the baking temperature of the baking process is 0.96×1200=1152°C, and the baking time of the baking process is 0.96×3=2.88h.
[0055] Step S6, baking the candidate raw material based on the determined baking control parameters, and cooling the candidate raw material after baking to obtain a formed tundish dry material.
[0056] Specifically, step S6 includes: The demoulding strength of the candidate raw material after baking is detected, and whether the baking is completed is determined based on the demoulding strength.
[0057] It should be noted that those skilled in the art are aware that any device and method in the prior art that can detect the demoulding strength of the candidate raw material after baking falls within the protection scope of the present invention and will not be described in detail herein.
[0058] In implementation, if the demoulding strength of the candidate raw material after baking is greater than a preset demoulding strength, it is determined that baking is completed.
[0059] It can be understood that demoulding strength refers to the maximum external force that a material can withstand without breaking or deforming before or after being taken out of the mold during the molding process. If the demoulding strength is insufficient, the dry material in the tundish will crack, break or deform during the demoulding process, affecting the molding quality. The actual implementer can set the preset demoulding strength based on the actual situation or the average demoulding strength corresponding to the dry material in the tundish that has passed the qualification test in the historical data. Preferably, the preset demoulding strength is set in the range of 8MPa to 10MPa.
[0060] The present invention determines whether baking is completed based on the demoulding strength of the candidate raw material after baking, and can improve the strength and molding efficiency of the tundish dry material.
[0061] Specifically, in the step S6, the cooling rate of the cooling process is determined based on the baking control parameters.
[0062] It should be noted that those skilled in the art are aware that any device and method in the prior art that can cool the candidate raw material after baking falls within the protection scope of the present invention and will not be described in detail herein.
[0063] It is understandable that the cooling rate can be set to 1 / 3 to 1 / 5 of the heating rate.
[0064] The present invention determines the cooling rate of the cooling process based on the baking control parameters, can avoid cracks caused by too fast temperature changes, reduce thermal expansion and contraction caused by temperature changes, thereby improving the strength of the tundish dry material and extending the service life.
[0065] The present invention can remove moisture and avoid expansion and rupture of the intermediate bag dry material by drying the candidate raw materials after crushing, grinding and mixing, thereby improving the strength and molding efficiency of the intermediate bag dry material after molding. By determining the vibration parameters through the particle size distribution after drying, not only can the particles in the dry material be rearranged to form a dense and uniform whole, thereby improving the strength of the intermediate bag dry material, but also the vibration and molding efficiency can be improved. By determining whether the density of the candidate raw materials after vibration meets the preset standards, the uniformity and tightness of the intermediate bag dry material can be further ensured. The baking control parameters of the baking process are determined through the volume density and apparent porosity after vibration, and the baking process can be flexibly controlled according to the parameters after vibration, thereby improving the strength and molding efficiency of the intermediate bag dry material, and extending the service life of the intermediate bag dry material.
[0066] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A high-performance continuous casting tundish dry material forming method, characterized in that: include: Step S1, crushing and grinding the raw materials, and stirring and mixing them according to the formula ratio to obtain candidate raw materials; Step S2, drying the candidate raw material and obtaining the particle size distribution of the candidate raw material after drying; Step S3, determining vibration parameters during the vibration process according to the particle size distribution, and performing vibration treatment on the dried candidate raw material based on the vibration parameters; the vibration parameters include vibration time and vibration frequency; Step S4, obtaining the volume density and apparent porosity of the candidate raw material after vibration, and determining whether the density of the candidate raw material after vibration meets a preset standard according to the volume density and apparent porosity; Step S5, if the density of the candidate raw material after vibration meets the preset standard, determining the baking control parameters of the baking process based on the bulk density and the apparent porosity; the baking control parameters include heating rate, baking temperature and baking time; Step S6, baking the candidate raw material based on the determined baking control parameters, and cooling the candidate raw material after baking to obtain a formed tundish dry material.
2. The high-performance continuous casting tundish dry material forming method according to claim 1, characterized in that: In step S3, determining the vibration parameters during the vibration process includes: Step S31, determining a particle size characteristic value according to the particle size distribution; Step S32, comparing the particle size characteristic value with a preset particle size value, and determining the vibration parameters during the vibration process based on the comparison result.
3. The high performance continuous casting tundish dry material forming method according to claim 2, characterized in that: In the step S32, the vibration parameters in the vibration process are determined, which further includes: If the particle size characteristic value is greater than the preset particle size value, increasing the preset vibration parameter to obtain each vibration parameter in the vibration process; If the particle size characteristic value is less than or equal to the preset particle size value, the preset vibration parameter is reduced to obtain each vibration parameter in the vibration process; wherein the preset vibration parameter is the vibration parameter in the vibration process corresponding to the preset particle size value.
4. The high performance continuous casting tundish dry material forming method according to claim 3, characterized in that: In the step S32, the increase / decrease amplitude of the preset vibration parameter is determined according to the difference between the particle size characteristic value and the preset particle size value.
5. The high performance continuous casting tundish dry material forming method according to claim 4, characterized in that: In step S4, if the volume density is greater than the preset volume density and the apparent porosity is less than the preset apparent porosity, the density of the candidate raw material after vibration meets the preset standard; otherwise, the density of the candidate raw material after vibration does not meet the preset standard.
6. The high-performance continuous casting tundish dry material forming method according to claim 5, characterized in that: In the step S4, it also includes: Step S41, if the density of the candidate raw material after vibration does not meet the preset standard, repeat step S3 to perform vibration treatment.
7. The high performance continuous casting tundish dry material forming method according to claim 6, characterized in that: In the step S5, determining baking control parameters of the baking process based on the bulk density and the apparent porosity includes: The volume density and the apparent porosity are input into a target neural network model to obtain baking control parameters output by the target neural network model.
8. The high performance continuous casting tundish dry material forming method according to claim 6, characterized in that: In the step S5, determining baking control parameters of the baking process based on the bulk density and the apparent porosity includes: Step S51, determining a parameter adjustment ratio based on the volume density and the apparent porosity; Step S52, determining the baking control parameters of the baking process based on the parameter adjustment ratio and the preset baking control parameters.
9. The high performance continuous casting tundish dry material forming method according to claim 7 or 8, characterized in that: In the step S6, it includes: The demoulding strength of the candidate raw material after baking is detected, and whether the baking is completed is determined based on the demoulding strength.
10. The high performance continuous casting tundish dry material forming method according to claim 9, characterized in that: In the step S6, a cooling rate of the cooling process is determined based on the baking control parameters.
Citation Information
Patent Citations
Coke out-of-furnace baking process
CN112410051A
Preparation method of sodium ion battery positive electrode material based on atomic layer deposition
CN117117134A
Preparation method of self-curing tundish dry material
CN119658804A
Estimation for baking temperature of enamel
JP1986142449A
Cited By
Preparation system and method of high-performance tundish dry material
CN120306617A
A system and method for preparing high-performance tundish dry material
CN120306617B